The Defensive Consumer: Advertising Deception, Defensive Processing, and Distrust - Darke, Peter R; Ritchie, Robin J.B (Journal of Marketing Research, 2007)
Abstract The authors show that deceptive advertising engenders distrust, which negatively affects people's responses to subsequent advertising from both the same source and second-party sources. This negative bias operates through a process of defensive stereotyping, in which the initial deception induces negative beliefs about advertising and marketing in general, thus undermining the credibility of further advertising.